2003
DOI: 10.1177/230949900301100112
|View full text |Cite
|
Sign up to set email alerts
|

The Shape and Size of Femoral Components in Revision Total Hip Arthroplasty among Chinese Patients

Abstract: Chinese patients are likely to need smaller femoral components than Caucasian patients, and may benefit from bowed-stem components in femoral revision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Ethnic differences have not received much focus given that most research has been aimed at the investigation of shape differences within the Caucasian population [24, 6, 10, 11, 17, 2123]; however, previous studies have reported the anatomy and comparison of East Asian populations (Japanese, Chinese, Indian) to existing implant systems [3, 4, 10, 11, 2123, 26]. We therefore asked: (1) Do shape differences in the distal femur and proximal tibia exist among different ethnic groups?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethnic differences have not received much focus given that most research has been aimed at the investigation of shape differences within the Caucasian population [24, 6, 10, 11, 17, 2123]; however, previous studies have reported the anatomy and comparison of East Asian populations (Japanese, Chinese, Indian) to existing implant systems [3, 4, 10, 11, 2123, 26]. We therefore asked: (1) Do shape differences in the distal femur and proximal tibia exist among different ethnic groups?…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported the anatomy and comparison of East Asian populations (Japanese, Chinese, Indian) to existing implant systems [3, 4, 10, 11, 2123, 26]. Anatomic differences have been identified between both sex and ethnicity, with Caucasian subjects having a higher tibial torsion angle and lower varus alignment than Japanese [12].…”
Section: Introductionmentioning
confidence: 99%
“…Other authors reported that significant anterior cortical thinning ( Figure 4) was more common in Chinese patients if 200-mm straight stems were used and suggested using bowed 200-mm femoral components instead. 26 Onlay structural bone graft is augmented for supporting thinning cortex or intraoperative perforation. Emerson et al 27 reported that onlay graft united in an average of 8.4 months through a healing process with round-off, followed by partial and complete bridging.…”
Section: Discussionmentioning
confidence: 99%
“…5 Another Chinese study also highlighted the need of smaller sized femoral component for Chinese population. 6 The study in 337 knees have compared the aspect ratio in males and females, found that higher aspect ratio for femur and tibia in smaller size knees, mainly in females. 7 Mahfouz M et al has published a three-dimensional morphology data of 1000 knees comparing African Americans, East Asians and Caucasians.…”
Section: Introductionmentioning
confidence: 99%